Norden as an argument : The 1994 EU-referenda in Helsingin Sanomat, Dagens Nyheter and Aftenposten - Nygrund, Heidi Madeleine (Helsingfors universitet, 2012)
The dramatic changes in Europe after the end of the Cold War and the dissolution of the Soviet Union made the early 1990s an important transition period. The Nordic third way between American capitalism and Soviet communism lost significance and the economic recession in Finland and Sweden led to cutbacks in the famous welfare systems. The Nordic countries Finland, Sweden and Norway became economically and politically dependent on the European Union and eventually applied for EU-membership. The three referenda were held in the autumn of 1994. Finland and Sweden approved of EU-membership, while the Norwegians voted no. This thesis looks at how Norden, the geographical and historical region consisting of the five Nordic countries Denmark, Finland, Iceland, Sweden and Norway, coped with this new situation by analysing how Norden was presented as an argument in the debate leading up to the referenda. Using media content analysis, this study describes and analyses the use of Norden in the editorial pages of the three major Nordic newspapers Helsingin Sanomat in Finland, Dagens Nyheter in Sweden and Aftenposten in Norway. The analysis comprises approximately one month of editorial pages from each newspaper. The study also discusses how a Nordic identity was visible in the sources. A unique code schedule was developed in order to show in which thematic circumstances Norden appeared as well as which attitudes were used in the coverage of Norden. The study has three main findings. Firstly, contrary to what many scholars believed in the early 1990s, Norden never lost value for the Nordics but simply fell out of fashion when the EU became a more attractive alternative. Secondly, the Nordic interdependence remained strong although the Nordic reality was shaken. And thirdly, the belief that Norden was better than others still prevailed. An additional finding is that Nordic identity, although not explicitly mentioned in the editorials, permeated the whole debate on Norden. For the Nordic countries, Norden is an additional ...